Entrepreneurship Management Skills Needed by Self-Employed Motor Vehicle Mechanics in the North Central States of Nigeria - Abdulkadir, M.; Ma’aji, S. A.; Okwori, R. O.; Mustapha, A. (Kashere Journal of Education, 2021)
This study identified the entrepreneurship management skills needed by self-employed motor vehicle mechanics in the North-Central States of Nigeria. Two research questions and two null hypotheses guided the study. A descriptive survey research design was employed for the study. The study was carried out in the North-Central States of Nigeria. The targeted population for this study was 22,523 respondents. The sample for the study was 2,019 respondents comprising 1,435 registered self-employed motor vehicle mechanics, drawn through the use of the Taro Yamane formula for finite populations; 475 managers of micro firms in motor vehicle mechanics; and 109 entrepreneurship lecturers. A structured questionnaire titled ’Self-Employed Motor Vehicle Mechanics Entrepreneurship Management Skills Needed Questionnaire (SEMVMEMSNQ) developed by the researchers and validated by five Lecturers in the Department of Industrial and Technology Education, Federal University of Technology, Minna, was used for the data collected for the study. The reliability coefficient of the instrument was 0.84, established through Cronbach’s Alpha Statistical techniques. Mean and standard deviation were the statistical tools used to analyse the data for answering the research question. While One-Way Analysis of Variance (ANOVA) statistics was employed to test the null hypotheses for the study at the .05 level of significance. The findings of the study revealed, among others, that all the 13 items of entrepreneurial accounting skills and public relations skills are highly needed by motor vehicle mechanics in the North Central States of Nigeria. Based on the findings, it was recommended, among others, that: The National Council on Automotive (NCA) should, in collaboration with the Federal Ministry of Labour and Productivity, incorporate the identified entrepreneurial skills into their training and retraining programmes so that motor vehicle mechanics can be made to acquire the needed entrepreneurship management skills that will assist them to sustain and secure their employment.